Pengaruh Kompensasi, Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai pada Badan Arsip dan Perpustakaan Provinsi Aceh - Sarboini, Sarboini; Mariati, Mariati (Lembaga KITA, 2020)
This study aims to determine the effect of compensation, leadership style and work motivation on employee performance in the Archives and Library of Aceh Province. This research was conducted at the Archive and Library Agency of the Province of Aceh, with the object of research being the effect of compensation, Leadership Style and work motivation on employee performance at the Archive and Library Board of the Province of Aceh. This analysis is based on data obtained from 181 population determination of the sample in this study using the Slovin formula, which is 44 people sampled. In this study, the data analysis method used is multiple linear regression analysis methods (Multiple Linear Regression) which are processed with the SPSS (Statistical Product and Service Solution) program. The results of the study based on the F test (simultaneously) obtained an F-count of 24.196 while the Ftable at a significant level Î± = 5% was 3.225. This shows that Fcount> F table, with a significance level of 0,000. The results of this calculation can be drawn a conclusion that accepting the null hypothesis, meaning that the compensation variable (X1) leadership style (X2) and work motivation (X3), jointly have a significant effect on employee performance at the Aceh Provincial Archives and Library Board. This means that overall respondents agreed to the indicators examined, thereby affecting the performance of employees at the Aceh Provincial Archives and Library Board. While partially from the three variables examined, it turns out that the compensation variable (X1) which has a dominant influence on employee performance at the Aceh Provincial Archives and Library Agency, because the regression coefficient is greater than the other variables.Â Keywords: compensation, leadership style, work motivation, employee performance.